An Analysis of Word Formation Process of English Slang Used in Camp Rock Movie Script - Sopiah, Siti; Yulianisha, Della (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
This study analyzes the process of forming words from slang words in the Camp Rock film script. This study uses the word formation process theory from George Yule (2014) to analyze how the process of forming slang words in the Camp Rock film script and find out which type of word formation is the most dominant used in the Camp Rock film script. The research method used is descriptive method, namely collecting data and then analyzing it descriptively. The researcher found 5 types of slang word formation in this film script, consisting of clipping, derivation, compounding, acronym and blending. This study found that the most dominant type of word formation used in this film was clipping with a percentage of 57%, then followed by acronyms with a percentage of 19%, then blending with a percentage of 14%, and the last two namely derivation and compounding which only had a percentage of 5 %.